Regional cooling for reducing brain temperature and intracranial pressure Resfriamento cerebral regional para redução da temperatura e pressão intracraniana - Luis Vicente Forte; Cássio Morano Peluso; Mirto Nelso Prandini; Roberto Godoy; Salomon Soriano Ordinola Rojas (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the effectiveness of regional cooling for reducing brain temperature (BrTe) and intracranial pressure (ICP) in patients where conventional clinical treatment has failed. METHOD: Regional cooling was carried out using ice bags covering the area of the craniectomy (regional method) in 23 patients. The BrTe and ICP were determined using a fiber optic sensor. Thirteen patients (56.52%) were female. The ages ranged from 16 to 83 years (mean of 48.9). The mean APACHE II score was 25 points (11-35). The patients were submitted, on mean, to 61.7 hours (20-96) of regional cooling. RESULTS: There was a significant reduction in mean BrTe (p<0.0001-from 37.1ºC to 35.2ºC) and mean ICP (p=0.0001-from 28 mmHg to 13 mmHg). CONCLUSION: Our results suggest that mild brain hypothermia induced by regional cooling was effective in the control of ICP in patients who had previously undergone decompressive craniectomy. OBJETIVO: Avaliar a eficácia do resfriamento regional na redução da temperatura cerebral (TeCe) e pressão intracraniana (PIC) após falha das medidas clínicas convencionais de tratamento. MÉTODO: O resfriamento cerebral foi realizado com bolsas com gelo, colocadas sobre a área de craniectomia (método regional) em 23 doentes. A TeCe e PIC foram verificadas com sensor de fibra óptica. Treze (56,52%) eram do sexo feminino. A idade variou de 16 a 83 anos (média 48,96). A pontuação média no índice APACHE II foi 25 pontos (11-35). Os doentes foram submetidos, em média, a 61,7 horas (20-96) de resfriamento regional. RESULTADOS: Houve uma redução significativa da TeCe média (p<0,0001-de 37,1ºC para 35,2ºC) e da PIC média (p=0,0001-de 28 mmHg para 13 mmHg). CONCLUSÃO: Nossos resultados sugerem que o resfriamento regional foi eficaz no controle da PIC nos doentes submetidos, previamente, a craniectomia descompressiva.